Um modelo de sociedade ‘bem ordenada' em John Rawls - Pereira, Matheus Estevam (2021)
This dissertation aims to analyze a well-ordered society in John Rawls, which is based on justice as equity. The work aims to highlight, in the current Brazilian contemporary society, the theory of justice as equity that seeks to maximize the distribution of primary goods, essential to human dignity, in favor of the least favored, who are in the worst social position, without harming inviolability of individuality. Justice as equity has its origin in the original position, a contractual position, in which the parties are placed under the veil of ignorance, in order to establish the principles of justice in an impartial way. In the original position, the principles of justice with which everyone agrees and come to live in a liberal democratic cooperative system, convinced that primary goods will be distributed equitably, maximizing the distribution to the least favored. The main focus of this research is to analyze how the concept of person contributes, effectively to the defense of the original position and the principles of justice, thus enabling the defense of human rights in the perspective of the organization of a well-ordered society under the protection of freedom and equality. This research was elaborated by a reading of the classics of John Rawls, mainly the work: Political Liberalism. So, in order to understand what freedom and democracy are, we stick to their classics. And so, through this study, it is intended to demonstrate that the increasing intensification of cooperation between people was a main support with which Rawls influenced civil society.